Back Cover: A Multifunctional Bichromophoric Nanoaggregate for Fluorescence Imaging and Simultaneous Photogeneration of RNOS and ROS (Chem. Asian J. 11/2013). Issue 11 (28th October 2013) - Fraix, Aurore; Gonçalves, A. Ricardo; Cardile, Venera; Graziano, Adriana C. E.; Theodossiou, Theodossis A.; Yannakopoulou, Konstantina; Sortino, Salvatore
Abstract : Supramolecular Chemistry The fabrication of photoactivatable nanoconstructs of biomedical significance represents a challenging objective, in particular for multimodal imaging and therapy of cancer. In their Full Paper on page 2634 ff., Salvatore Sortino et al. present a multifunctional supramolecular ensemble displaying imaging and multiple photototoxic modalities in a single nanostructure. The reported construct, which is based on a porphyrin–β–cyclodextrin conjugate, is internalized by living cells, can be easily imaged subcellularly by fluorescence microscopy, lacks any dark toxicity, and can release nitric oxide and singlet oxygen under under the exclusive control of visible‐light stimuli (see the image on the Back Cover).